Diverse drivers of unsustainable groundwater extraction behaviour operate in an unregulated water scarce region. (15th April 2019) - Khair, Syed Muhammad; Mushtaq, Shahbaz; Reardon-Smith, Kate; Ostini, Jenny
Abstract: Depletion of groundwater resources is of increasing concern in many parts of the world; however, farmers' perceptions of resource status and the role these have in influencing decisions about groundwater use are rarely considered and even more rarely analysed. This paper investigates the links between farmers' perceptions of resource condition and drivers of groundwater decline and patterns of groundwater use in the semi-arid highland region of Balochistan, Pakistan. Key factors associated with groundwater over-exploitation in this region, identified by farmers, include: high returns from irrigated fruit and vegetable cultivation; drought; mass installation of tubewells; inefficient irrigation practices; government policies and subsidies that promote groundwater development; and lack of effective groundwater governance. Critically, while a majority of farmers in this study believe that groundwater is a limited resource, there is little evidence to indicate that this then leads to sustainable groundwater use decision making within these communities. Without effective intervention, groundwater resources in this region will potentially suffer the consequences of human behaviour associated with the use of common pool resources identified in Hardin's (1968) seminal 'Tragedy of the Commons' paper. This study exemplifies the importance to the future of rural communities in water scarce regions of effective governance, regulations and economic incentives for sustainable water management. Highlights: We investigated farmers' perceptions in relation to groundwater use in a water scarce unregulated environment. Multiple factors were found to be associated with groundwater over-use. Awareness that groundwater is limited did not alter extraction behaviour. Perverse incentives, maladaptation and policy making on the run were apparent. We discuss governance options for sustainable resource use in water scarce regions.